Epidemiological analysis of TB-HIV comorbidity in Medan City, 2022–2024 - Dwi Mawandri; Nurhayati Nurhayati; Nofi Susanti; Hasrat Efendi Samosir (Poltekkes Kemenkes Bandung, 2026)
Background: TB-HIV comorbidity represents a significant public health challenge due to biological interactions that elevate mortality. In Medan City, transmission is exacerbated by high population density, yet its distribution patterns remain poorly delineated. Objective: This study aimed to analyze the epidemiological data based on person, place, and time variables of TB-HIV cases in Medan City (2022–2024). Methods: This descriptive quantitative observational study utilized secondary data from all reporting healthcare facilities (Primary Health Centers, hospitals, and lung clinics) in Medan City. Data were obtained via the SITB 03 SO form (the Tuberculosis Information System’s Drug-Sensitive Tuberculosis Patient Register) from the North Sumatra Provincial Health Office, using a total sampling technique (820 cases). Microsoft Excel's pivot table features were employed for data cleaning and variable categorization, followed by descriptive analysis, calculating frequency, proportions, and annual trends. Results: Treated cases increased (from 177 cases in 2022 to 322 cases in 2023) and stabilized in 2024 (321 cases). Comorbidity was predominantly found in males and the productive age group of 18–59 years. Geographically, Medan Marelan District recorded the highest accumulation of cases. Conclusion: Case dynamics reflect strengthened SITB (Tuberculosis Information System) surveillance. These findings serve as a foundation for mapping intervention areas. The Medan City Health Office is advised to expand bidirectional screening into private facilities to capture unrecorded cases, and to optimize digital treatment monitoring alongside cadreled assistance to mitigate loss to follow-up among productive age male patients.